Military casualties and exchange rates during the First World War: did the Eastern Front matter?1. (28th September 2018) - Duarte, Pablo; Freidinger, Marcel; Hoffmann, Andreas
Abstract: Although the First World War was ultimately decided in the west, historians have emphasized the importance of the often 'forgotten' Eastern Front in understanding its complex evolution. This article examines the perception of contemporary foreign exchange traders concerning the relative importance of the Eastern Front over time. Using a newly compiled dataset on prisoners of war and on soldiers killed and wounded, we show that traders were concerned with casualties on both fronts, recognizing the significance of the two‐front war in the early war years. From the autumn of 1916 onwards, traders seemed to believe the key to winning the war lay in the west only.